Mini Tinjauan Literatur Pemanfaatan Software Mathway untuk Berfikir Komputasi Siswa - Yulia Nasution; Yahfizham (INDO PUBLISHING, 2025)
Strong mental capacity for computation is essential in the 21st century, especially for students who aim to gain systematic and efficient mathematical understanding. The purpose of this study was to examine the use of the Mathway application in promoting students' computational thinking skills. This study analyzed the literature of ten scientific articles that supported the research. The use of Mathway was found to improve the understanding of mathematical concepts, motivate learning habits, and encourage critical thinking. It is important to use Mathway carefully so that students can not only rely on direct solutions but also understand the thought process behind problem solving. Therefore, this application should be viewed as a learning aid that encourages the process of learning mathematics to be efficient.